Prevalence of Impacted Canine and Associated Anomalies among Patients at King Fahad Hospital In Madinah – A Radiographic Study - Abdulmoeen E. Alhejali; Mohammed W. Alharbi; Ahmad A. Al-Fraidi; Ali S. Alshehri; Abdulrahman H. Alsaadi; Majdi M. Balquroun (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Introduction: The impaction of tooth have been studied by many authors and various terminologies have been given in the literature to define impaction including delayed eruption, primary retention, submerged teeth, impacted teeth. According to Abron et al, impaction can be defined as a deceleration of the normal eruption process of the tooth and according to Lindauer et al, it can be defined as a impaction if it was not erupted after completion of the root development. Methods: A Radiographic Study study will include all orthopantomogram for the subjects aged 14 to 40 who presented to specialized dental center of King Fahad in Madinah from 2015 to 2017. The data will be collected in Excel sheet and analyzed by SPSS VER 20. Results: In this study 928 Orthopantograms (OPGs) for patients their ages range from 14 to 40 year, with Mean ± S.D of age was 21.5±7.5, were assessed for permanent canine impaction, 19.7% (183 ) had impacted canines and 80.3% were without impaction. Conclusion: The prevalence of canine impaction in a Madina city of Saudi Arabia was 5.35%, while no significant gender differences was observed